Buffers and their role in the nutritional preparation of athletes - Jones, A. M. (Sports Science Exchange, 2014)
Key Points: Performance during continuous or intermittent high-intensity exercise can be limited, at least in part, by the accumulation of hydrogen ions (H+) which reduce muscle pH and interfere with muscle contractile and metabolic processes. H+ accumulation in the muscle cells and blood can be buffered in many different ways, but few of these can be altered by nutrition. The exceptions are the intracellular buffer, carnosine, and the extracellular buffer, bicarbonate. Nutritional interventions with carnosine and bicarbonate might therefore enhance fatigue resistance and improve performance during high-intensity exercise. Muscle carnosine concentration can be increased by dietary supplementation with ß-alanine (approximately 3-6 g of ß-alanine per day for 4-8 wk) whereas extracellular bicarbonate concentration can be increased by about 20% following ingestion of sodium bicarbonate (~0.3 g per kg body mass 1-2 h before exercise). There is evidence that both ß-alanine and sodium bicarbonate ingestion can enhance exercise performance during single or repeated bouts of high-intensity exercise in which energy is supplied predominantly through anaerobic glycolysis. Sodium bicarbonate supplementation can produce gastrointestinal disturbances. ß-alanine supplementation in doses greater than 10 mg/kg BM can lead to a short period of paresthesia (flushing and a prickling sensation on the skin) although recent "slow-release" supplements have largely overcome these unpleasant side effects. To ensure that the potential benefit of supplementation with bicarbonate or ß-alanine outweigh any negative side effects, it is important for athletes to practice their supplementation strategy prior to competition.